Ethno-veterinary medicinal plants and modes of their traditional application to cure animal ailments in Adaa’Liben district, Ethiopia - Ijigu Asefa (Hawassa University, 2021)
Cross-sectional survey of ethno-veterinary medicinal plants was carried out from November 2016 to April 2017 in Ada’a-Liben district, Ethiopia. The purposes of the study were to identify and document medicinal plants, animal ailments treated by the medicinal plants, and modes of preparation of the medicinal plants for the treatment of animals in the study area. Rapid appraisal methods were used to gather relevant information to select study kebeles and identify the 31 informants including traditional healers. Information about the medicinal plants and their usage to cure various animal ailments were gathered through a semi-structured questionnaire, field observation, group discussion and market survey. Thirty one ethnoveterinary medicinal plant species belonging to 23 families were used to treat 24 livestock ailments in the study area. Among the medicinal plants, Zingibera officinale, Solanium incanum, Withania somnitera, and Allium sativum were used to treat blackleg and respiratory diseases whereas Cypresnivies, Cordia africana, Celtisa africana, and Vernonia amygdalina serve for deworming animals. Fresh moist medicinal plants (51.6 %, n = 16/31) were the most frequently used in preparing remedies comparing to dry plants (48.4 %, n = 15/31). The widely used plant part was leaf (51.6 %) followed by fruit, seed and root (each 9.7 %) and leaf/fruit/root mixed, seed/pods, leaf/seed/stem, leaf/root, stem and bulb (each 3.2 %). The modes of preparation of medicinal plant remedies were found to be chopping (35.5 %), grinding (25.8 %), crushing (19.4 %) , decoction and using medicinal plants without processing (6.5 % each), and socking and crushing/shopping (3.2 % each). The most widely used route of administration of these remedies was oral (77.4 %) followed by topical (19.4 %) and nasal (3.2 %). Eighteen species of the medicinal plants were used to traditionally treat more than one animal ailment while the remaining 13 were used to cure only one ailment each. Agricultural expansion was the highest threat for the ethnoveterinary medicinal plants (51.6 %, n = 16/31) followed by drought (19.4 %, n = 6/31), soil erosion and deforestation (9.7 %, n = 3/31 each). In conclusion medicinal plants and remedies derived from them are still important and readily available source of livestock health-care to rural people in the study area. Awareness creation work for traditional healers and further research on formal in-vivo and in-vitro experimental trails are suggested for a sustainable and efficient utilization of these medicinal plants.